1982
DOI: 10.1073/pnas.79.10.3295
|View full text |Cite
|
Sign up to set email alerts
|

Markedly elevated specific renin levels in the adrenal in genetically hypertensive rats.

Abstract: The specific renin (EC 3.4.99.19) activity in the adrenal of spontaneously hypertensive rats was determined by a method that is capable of distinguishing renin from nonspecific renin-like activity ofproteases by using specific antibody to renin. The renin level in the adrenals of adult spontaneously hypertensive rats with established hypertension was found to be 6-8 times as high as that of the normotensive control Wistar-Kyoto strain. The large difference in the adrenal renin level was observed even in 3-wk-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 48 publications
3
34
0
Order By: Relevance
“…Previously Naruse and Inagami 6 showed that adrenal renin continued to increase after bilateral nephrectomy when plasma active renin was very low; we confirmed these results and demonstrated that the increase in renin was confined to the zona glomerulosa cells.…”
Section: -13supporting
confidence: 78%
“…Previously Naruse and Inagami 6 showed that adrenal renin continued to increase after bilateral nephrectomy when plasma active renin was very low; we confirmed these results and demonstrated that the increase in renin was confined to the zona glomerulosa cells.…”
Section: -13supporting
confidence: 78%
“…Secretion of renin by the kidney increases in these conditions and renin in plasma may act upon its substrate to generate AI. However, renin is present in many organs (3)(4)(5)(6) and cell types (7)(8)(9), including vascular smooth muscle cells (8); AI and All and converting enzyme exist in renin-containing cells (7,9,10); and the plasma concentration of All is in the picomolar range (1 1), but binding affinities of this peptide to its receptors are in the nanomolar range (12)(13)(14)(15). These observations raise questions about the role of circulating renin and angiotensin.…”
Section: Introductionmentioning
confidence: 99%
“…29 Although the exact physiological function of intra-adrenal renin is unclear, local generation of Ang I and II may play a modulatory role in aldosterone secretion by affecting activity of biosynthetic enzymes or angiotensin receptors. In view of the reduced Ang II receptors we found in SHR, it is of interest that Naruse and Inagami 30 have reported markedly increased adrenal renin content in SHR. Although we did not measure adrenal renin content in our studies, it seems quite possible that the abnormal regulation of receptors we observed could be related to abnormalities in local, intra-adrenal, or periadrenal Ang II generation.…”
Section: Adrenal Ang II Receptor Regulationmentioning
confidence: 90%